Evaluation of Novel Food Additives on Product Acceptability in France - Petit, Sophie (International Journal of Food Sciences, 2024)
Purpose: The aim of the study was to analyze the evaluation of novel food additives on product acceptability in France. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: This study evaluating novel food additives on product acceptability in France, it was found that natural and organic additives significantly enhanced consumer acceptance. The additives were primarily valued for their perceived health benefits and minimal processing. Taste testing revealed that products with natural flavors and colors were preferred over those with synthetic counterparts. However, there was resistance among certain demographics, particularly older consumers, who showed a preference for traditional flavors. Overall, the study suggests that while novel additives can increase acceptability, consumer education and transparent labeling are crucial for widespread adoption. Unique Contribution to Theory, Practice and Policy: Theory of planned behavior (TPB), diffusion of innovations theory & expectancy-value theory may be used to anchor future studies on analyze the evaluation of novel food additives on product acceptability in France. Implement educational programs that inform consumers about the benefits and safety of novel food additives. Advocate for the development of clearer, more consistent regulatory guidelines for novel food additives to ensure safety and quality across markets.